A Literature Review: The Used of PROSPER Model in Guidance and Counseling Services for Improving Students Mental Health - Kristiana Firdausi (Universitas Sebelas Maret, 2019)
Internationally, in the past two decades, the issue of mental health has been the subject of discussion in the world health forum. Since 1946, at the International Health Conference, WHO released the definition of healthy humans as a condition in which an individual achieves